Impact of Volatility Spillovers upon Electric Utilities during the Russia-Ukraine Conflict - Nawaz, Farrukh; Khan, Mrestyal; Kayani, Umar; Pradipta, Indry Aristianto; Aziz, Aulia Luqman (International Journal of Energy Economics and Policy, 2024)
Considering the period of crises, the fluctuations in the stock market returns increase sharply. Consequently, volatility spillovers are observed across the equities. Thus, this paper investigates the volatility spillovers across the sector indices of the Russian economy during the ongoing Russia-Ukraine conflict (2022). For this purpose, the Diebold and Yilmaz (2012) spillover index methodology was used to model the risk spillover effects among the ten stock market sectors namely; chemicals, consumer, electric utilities, financials, metal and mining, oil and gas, telecommunications, and transport throughout February 24th, 2022-May 31st, 2023. The empirical findings showed significant volatility transmissions across the stock market sectors. Moreover, the market sectors including chemicals, electric utilities, transport, and telecommunications were the net recipients of the volatility spillovers. Meanwhile, the sectors consumer, financials, metal and mining, and oil and gas were recognized as the net transmitters. Furthermore, these findings provide useful implications for policymakers to investigate the volatility spillovers across stock market sectors, especially during times of crisis. Additionally, the empirical findings assist investors in gaining insight regarding the diversification of the investor’s portfolio assets to optimize returns, forecast possible future volatilities, and construct optimal portfolios.